Mothers going to war: The role of nurse practitioners in the care of military mothers and families during deployment. Issue 5 (3rd December 2012) - Agazio, Janice; Hillier, Shannon L.; Throop, Meryia; Goodman, Petra; Padden, Diane; Greiner, Shawna; Turner, Annette
Abstract Purpose Many military women are being called to separate from their children to go to war. Most previous research has focused upon paternal, rather than, maternal, separation. The purpose of this article is to describe the experience of military mothers and their children during wartime deployments with clinical implications for nurse practitioners (NPs) in military or community settings. Data sources Using grounded theory methods, 37 active duty and reserve component military women participated in a one‐time interview. Included were women who deployed for at least 4 months to Iraq or Afghanistan and had at least one child under the age of 12 during the separation. Conclusions Military families present unique challenges for NPs. Mother deployments offer opportunities for intervention and anticipatory guidance across the trajectory of the separation. Military women's emotional and physical health must be supported before, during, and following deployment. Implications for practice NPs are ideally positioned to support military families. During deployment, the NP's focus may shift to care of the children and their caregiver. Before and at reintegration, NPs are in a key position to intervene early for posttraumatic stress and support family readjustment.